Earnings Responses to Disability Benefit Cuts - Silvia Garcia Mandico; Pilar Garcia-Gomez; Anne C. Gielen; Owen O'Donnell (Institute of Labor Economics (IZA), 2018)
Using Dutch administrative data, we assess the work and earnings capacity of disability insurance (DI) recipients by estimating employment and earnings responses to benefit cuts. Reassessment of DI entitlement under more stringent criteria removed 14.4 percent of recipients from the program and reduced benefits by 20 percent, on average. In response, employment increased by 6.7 points and earnings rose by 18 percent. Recipients were able to increase earnings by exteuro0.64 for each exteuro1 of DI income lost. Female and younger recipients, as well as those with more subjectively defined disabilities, were able to increase earnings most. The earnings response declined as claim duration lengthened, suggesting that earnings capacity deteriorates while on DI. The deterioration was steepest for male, younger and fully disabled recipients. Working while claiming partial disability benefits appears to slow the deterioration of earnings capacity.
Keywords: H53; H55; J14; J22; 330; disability insurance; health; employment; earnings